Dysfunctional uterine bleeding: pathological aspects. - Vega Rizo Patrón, L. (2015)
In the period between 1969 and June 1974, we had the opportunity to study in the Department of Pathology of the Hospital Daniel A. Carrion, corresponding to 4,643 Endometriosis patients with bleeding of endometrial origin.